The Effects of Different Density Microneedles on Melatonin Release (Journal of Fiber Bioengineering and Informatics, 2022)
The effect of different microneedles (MNs) densities on drug release was studied by using silk fibroin with good biocompatibility as the substrate of microneedles. The mixture of D-sorbitol and silk fibroin at the ratio of 2:10 was poured into a polydimethylsiloxane mold. After vacuum extraction, constant temperature and humidity drying, the silk fibroin microneedles were obtained. Three kinds of microneedles arrays of different densities were prepared with the area of 1 ${\rm cm}^2:$ 5×5, 10×10 and 20×20. The length of silk fibroin microneedles was controlled at about 600 µm, and D-sorbitol/silk fibroin blend f ilm was used as the control group. Melatonin was selected as the model drug and three kinds of MNs and blend film were used to study the drug release in vitro experiment. The aggregation structure of D-sorbitol/silk fibroin MNs was measured by X-ray diffraction (XRD) and infrared spectroscopy. The anti-compression properties of three kinds of MNs were measured by texture analyzer (TMS-PRO). The results showed that: (1) D-sorbitol could change the silk fibroin from random coil structure to the crystal structure of Silk I, and the dissolution rate of Silk fibroin MNs was low and the swelling property of silk fibroin was certain. (2) All three types of MNs have good compression resistance and puncture performance. It can effectively open the channels for drug delivery and relieve pain. (3) All three types of MNs have good drug release properties. As the density of the MNs increases, the drug release rate and cumulative drug release rate increase. As the density of the MNs increases, the compression performance of the MNs is improved. All three types of silk fibroin MNs have good penetration effects and can achieve slow-release effects. Compared with silk fibroin film without MNs, silk fibroin MNs can significantly increase the drug release rate by opening skin micropores.
Keywords: Silk Fibroin; MNs; Drug Release; Melatonin; Crystal structure.